Dataset on endophytic and rhizoplane fungi on the roots of wild grapevine in Croatia and Bosnia and Herzegovina - Tomislav Radić (Data in Brief, 2021)
The data presented in this article are related to the research article entitled “Root-associated community composition and co-occurrence patterns of fungi in wild grapevine”. This dataset documents the diversity of endophytic and rhizoplane fungi found on the roots of 38 wild grapevine plants growing at four locations (Krka, Neretva, Psunj and Paklenica) in Croatia and Bosnia and Herzegovina. We record here 48 identified fungal operational taxonomic units (OTUs) from 3 phyla, 23 families and 30 genera. The material in this Data in Brief paper comprised the data on the identification of OTUs with their corresponding ecological niche, abundance distribution of each fungal OTU recorded in each of the host and location, restrictedness and with fit to the Sloan neutral community model.